Contributing Factors to Organizational Success: A Case Study of McDonald’s - Chia, Xin Rou; Kee, Daisy Mui Hung; Khor, Sue Ting; Chin, Kai Yee; Lok, Tzyy Xian; Almutairi, Hanouf Ali; Quttainah, Majdi Anwar; Balakrishnan, Hariharan; Kulkarni, Swati (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
McDonald’s is one of the most successful fast food companies around the world. It has approximately 32,000 outlets located in 119 countries. Being a global and modern fast food company, McDonald’s has a clear vision, “to be the world’s best quick service restaurant experience”. This paper presents the contributing factors which drive McDonald’s success being a global and modern fast food company. McDonald’s top management believes that job satisfaction and motivation are the contributing factors to the success of McDonald’s. McDonald’s has won many awards over the years for its employees’ engagement programs.